Respuesta :
Answer:
(option C/3) 12^3 + 6x^2
Step-by-step explanation:
Took test, got it right. Idk how, cause I was stump to.
Answer:
C. 12x³ + 6x²
Step-by-step explanation:
I'm an FLVS kid and got the question right, so I wanted to explain my answer:
You just have to use the distributive property for this one. Multiply 2x² by each term in the brackets.
2x²(6x + 3) ← original question for ref.
2x²(6x) = 12x³
- 2 · 6 = 12
- x² · x = x³
- ("x" techniqually has a placeholder exponent of 1. To multiply two exponents with the same base, you just add the exponents. So x2 + x1 = x3.)
2x²(3) = 6x²
- 2 · 3 = 6
- Keep the variable and exponent the same
So the new terms are 12x³ + 6x²
The answer is C.